Chlamydia psittaci inhibits apoptosis of human neutrophils by activating P2X7 receptor expression - Zhangping He; Chuan Wang; Jianye Wang; Kang Zheng; Nan Ding; Maoying Yu; Weiwei Li; Yuanyuan Tang; Yumeng Li; Jian Xiao; Mingxing Liang; Yimou Wu (International Journal of Medical Microbiology, 2022)
This study tested the hypothesis that Chlamydia psittaci (C. psittaci) survives and multiplies in human neutrophils by activating P2X7, a nonselective cationic channel receptor expressed constitutively on the surface of these cells. Findings illustrated that P2X7 receptor expression was enhanced in C. psittaci-infected neutrophils. C. psittaci was able to inhibite spontaneous apoptosis of neutrophils through mitochondrial-induced ATP release and IL-8 production. Importantly, inhibiting ATP activation of the P2X7 receptor with AZ10606120 promotes apoptosis, while stimulating P2X7 receptor expression with BzATP delayed spontaneous apoptosis of human neutrophils, suggesting that C. psittaci inhibits apoptosis of human neutrophils by activating P2X7 receptor. This study reveals new insights into the survival advantages of the latent persistent state of C. psittaci and the mechanism by which it evades the innate immune response.